Potential beneficial effects of whole-body vibration for muscle recovery after exercise - Kosar, A. C.; Candow, D. G.; Putland, J. T. (The Journal of Strength and Conditioning Research, 2012)
Whole-body vibration is an emerging strategy used by athletes and exercising individuals to potentially accelerate muscle recovery. The vibration elicits involuntary muscle stretch reflex contractions leading to increased motor unit recruitment and synchronization of synergist muscles, which may lead to greater training adaptations over time. Intense exercise training, especially eccentric muscle contractions, will inevitably lead to muscle damage and delayed onset muscle soreness, which may interfere with the maintenance of a planned training program. Whole-body vibration before and after exercise shows promise for attenuating muscle soreness and may be considered as an adjunct to traditional therapies (i.e., massage, cryotherapy) to accelerate muscle recovery.